2016
DOI: 10.1098/rsos.160107
|View full text |Cite
|
Sign up to set email alerts
|

The taming of the neural crest: a developmental perspective on the origins of morphological covariation in domesticated mammals

Abstract: Studies on domestication are blooming, but the developmental bases for the generation of domestication traits and breed diversity remain largely unexplored. Some phenotypic patterns of human neurocristopathies are suggestive of those reported for domesticated mammals and disrupting neural crest developmental programmes have been argued to be the source of traits deemed the ‘domestication syndrome’. These character changes span multiple organ systems and morphological structures. But an in-depth examination wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
258
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(266 citation statements)
references
References 150 publications
(217 reference statements)
4
258
1
3
Order By: Relevance
“…It has recently been suggested that the domesticated phenotype could be caused by a general embryological effect acting on the neural crest cells (Sánchez-Villagra et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been suggested that the domesticated phenotype could be caused by a general embryological effect acting on the neural crest cells (Sánchez-Villagra et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although the domestication of each species must have involved direct or indirect selection for docility (lack of fear) and tameness (ability to be handled by humans), the domesticated breeds of the different mammalian species all share a distinctive suite of physical and physiological traits, not seen in their wild progenitors. The suite of traits is neither universal amongst species nor amongst all breeds of a given species (Sanchez-Villagra et al, 2016). Nevertheless, it is sufficiently generic to be seen as a signature feature of mammalian domestication.…”
mentioning
confidence: 99%
“…The particular secondary morphological and physiological traits that mark the domesticated state include: floppy ears, smaller jaws, smaller teeth, pigmentation changes in the coats (toward white and brown spots), reductions in adrenocortical hormone titers, increased frequency of estrus cycles, reduction in brain size, and alterations in concentration of several brain neurotransmitters. (For a comprehensive tally of which domestication-specific traits appear in the different mammalian species that have been domesticated, see Figure 1 of Sanchez-Villagra et al, 2016. ) This condition has been dubbed the "domestication syndrome", abbreviated here as the DS.…”
mentioning
confidence: 99%
“…Behavioural changes include reduced fear, aggressiveness and antipredator responses, increased sociability, and altered vocalization patterns [1,[13][14][15][16]. As summarized by Sánchez-Villagra et al [17], the dog is the clearest example of a domestic species with the highest account of phenotypic changes.…”
Section: '[Domestication Is] That Process By Which a Population Of Anmentioning
confidence: 99%